Pengaruh Kompetensi dan Lingkungan Kerja Terhadap Kinerja Pegawai - Septya Yolanda; Surajiyo, Surajiyo; Nasruddin, Nasruddin; Ronal Aprianto (Yayasan Literasi Sains Indonesia, 2023)
The purpose of this study was to determine the effect of competence and work environment partially and simultaneously on employee performance at the Office of Industry and Trade of Lubuklinggau City. The population and sample used amounted to 48 employees. This research uses quantitative research methods. The results obtained 1) Competence has a partially significant effect on Employee Performance at the Office of Industry and Trade of Lubuklinggau City with tcount = 7.201 > ttable = 1.677 significant 0.000 <0.05; 2) Work environment has a partially significant effect on employee performance at the Office of Industry and Trade of Lubuklinggau City with tcount = 6.919 > ttable = 1.677 significant 0.000 <0.05; 3) Competence and work environment have a significant effect simultaneously on employee performance at the Office of Industry and Trade of Lubuklinggau City with Fcount = 40.478 > Ftable = 3.20, significant 0.000 <0.05. The conclusion is that competence and work environment have a partial and simultaneous effect on employee performance at the Office of Industry and Trade of Lubuklinggau City.